Computational and Experimental Characterization of a Cagelike Fe15 Polycation1. Issue 10 (7th January 2013) - Hou, Yu; Fang, Xikui; Kwon, Kideok D.; Criscenti, Louise J.; Davis, Danae; Lambert, Tim; Nyman, May
Abstract: Polynuclear open‐shell transition‐metal clusters are synthetically challenging, yet fascinating from the perspective of their diverse properties. Iron clusters in particular can exhibit interesting magnetic and electrochemical behaviour, and they can potentially be exploited as models for geochemical processes at iron oxide surfaces. From solvothermal synthesis, we have obtained a cagelike polycationic Fe III cluster, [Fe15 Cl6 O6 (OH)2 (C3 H6 O2 )12 ] +, which features the common polyoxometalate (POM) Keggin ion trimer fragments oriented in an inverse fashion relative to the centre of the cluster. In addition to solid‐state structural characterization, we have examined the magnetic properties, which revealed the presence of antiferromagnetic exchange within the polynuclear system. Electrospray‐ionization mass spectrometry (ESI‐MS) revealed that the Fe9 core of the cluster remains intact upon dissolution, whereas the Fe–Cl 2+ caps are more labile. Computational studies agree well with the observed antiferromagnetic character, as well as the HOMO–LUMO bandgap, and also describe these frontier orbitals. Abstract : Iron polynuclear clusters have fascinating structures, magnetic properties, and bear strong structural resemblance to other discrete metal oxide clusters, as well as related synthetic and natural materials. Solvothermal synthesis has produced a Fe15 polynuclear cationic cluster that features trimer building blocks of the common Keggin cluster geometry, and square‐pyramidal Fe–Cl caps.